2008
DOI: 10.2134/agronj2008.0094
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation of Panicled Tick‐Clover, Tweedy's Tick‐Clover, and Tall Bush‐Clover: II. Herbage Nutritive Value and Condensed Tannin Concentrations

Abstract: Few native herbaceous perennial warm‐season legumes are available for cultivation in the southern United States. These would be useful for pastures, biomass production, wildlife plantings, rangeland reseeding, or native prairie restoration. Three native perennial legumes were selected from an initial screening of north Texas germplasm for potential domestication based on successful establishment, ease of seed harvest, and herbage production. Response to herbage removal was evaluated by measuring forage nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Foster et al (2007) and Muir et al (2005) reported whole‐herbage ADL concentrations for prairie acacia from 60 to 70 g kg −1 . Acid detergent lignin concentrations for 2008 were similar to those reported for other native perennial legumes by Muir et al (2008); however, ADL concentrations for 2009 in our study were greater than those previously reported.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Foster et al (2007) and Muir et al (2005) reported whole‐herbage ADL concentrations for prairie acacia from 60 to 70 g kg −1 . Acid detergent lignin concentrations for 2008 were similar to those reported for other native perennial legumes by Muir et al (2008); however, ADL concentrations for 2009 in our study were greater than those previously reported.…”
Section: Discussionsupporting
confidence: 84%
“…T here is growing interest among land managers in finding native, herbaceous perennial legumes to add species diversity to restored, indigenous plant communities or as forage sources for livestock and wildlife. Such uses include prairie and rangeland restoration, native grasslands reconstruction, cropland improvement, and many others (Muir and Bow, 2008; Muir et al, 2008). In the south‐central United States, for example, warm‐season perennial grasses provide the main source of forage for livestock and often peak in yield and quality between May and early July, with limited growth and declining nutritive value from mid‐July through mid‐September (Evers, 2008; Rao and Northrup, 2009).…”
mentioning
confidence: 99%
“…), prairie bundleflower ( Desmanthus leptolobus ), leadplant ( Amorpha canescens ), false indigo ( Amorpha fruticosa ) and Rhynchosia latifolia (Posler et al. , 1993; Muir and Bow, 2008; Muir et al. , 2008; Pitman, 2009b).…”
Section: What Needs Further Developmentmentioning
confidence: 99%
“…Natural pastures in South American temperate regions have been dramatically degraded because of overgrazing practices (Muir et al 2008). Furthermore, unfavourable environmental conditions (low temperatures, extended drought periods and low N content in soils) in arid and semiarid regions during winter contribute to restricted feed availability.…”
Section: Introductionmentioning
confidence: 99%